MANDARIN INTERFERENCE IN INDONESIAN LANGUAGE OF CHINESE COMMUNITY IN MAKASSAR CITY - Fathul Khair Tabri; Lukman; Ikhwan M. Said (International Journal of Social Science, 2022)
Interference is a language phenomenon that often occurs in Indonesian Languagelingual societies. This study reveals the Mandarin language interference that occurs in Indonesian speech in the Chinese community of Makassar City. This study concerns the main problem, namely how the form of interference that occurs in the Chinese community of Makassar City. The analyzed interference includes phonological, morphological, and syntactic interference. This study uses a descriptive qualitative approach. Data collection was done by direct observation, interviews, notes, and documentation. The presentation of the data results is done by collecting data, reducing data, presenting data, and drawing conclusions. The results of the study found that the phonological interference includes the addition of phonemes, changes in phonemes, and the release of phonemes. Likewise, there are two forms of morphological interference, namely lexical interference and reduplication. And syntactic interference occurs in the SKPO sentence structure pattern, the SKP sentence structure pattern (adverb of place), the SKP sentence structure pattern (adverb of time), and the question sentence pattern.